Pharmacotherapy with sertraline rescues brain development and behavior in a mouse model of CDKL5 deficiency disorder. (1st May 2020) - Fuchs, Claudia; Gennaccaro, Laura; Ren, Elisa; Galvani, Giuseppe; Trazzi, Stefania; Medici, Giorgio; Loi, Manuela; Conway, Erin; Devinsky, Orrin; Rimondini, Roberto; Ciani, Elisabetta
Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 ( CDKL5 ) gene cause a severe neurodevelopmental disorder, CDKL5 deficiency disorder (CDD). CDKL5 is fundamental for correct brain development and function, but the molecular mechanisms underlying aberrant neurologic dysfunction in CDD are incompletely understood. Here we show a dysregulation of hippocampal and cortical serotonergic (5-HT) receptor expression in heterozygous Cdkl5 knockout (KO) female mice, suggesting that impaired 5-HT neurotransmission contributes to CDD. We demonstrate that targeting impaired 5-HT signaling via the selective serotonin reuptake inhibitor (SSRI) sertraline rescues CDD-related neurodevelopmental and behavioral defects in heterozygous Cdkl5 KO female mice. In particular, chronic treatment with sertraline normalized locomotion, stereotypic and autistic-like features, and spatial memory in Cdkl5 KO mice. These positive behavioral effects were accompanied by restored neuronal survival, dendritic development and synaptic connectivity. At a molecular level, sertraline increased brain-derived neurotrophic factor (BDNF) expression and restored abnormal phosphorylation levels of tyrosine kinase B (TrkB) and its downstream target the extracellular signal-regulated kinase (ERK1/2). Since sertraline is an FDA-approved drug with an extensive safety and tolerability data package, even for children, our findings suggest that sertraline may improve neurodevelopment in children with CDD. This article is part of the special issue entitled 'Serotonin Research: Crossing Scales and Boundaries'. Highlights: Loss of CDKL5 causes a dysregulation of the expression of 5-HT receptors in the brain of Cdkl5 KO mice. Treatment with sertraline restores TrkB and ERK1/2 phosphorylation levels in the brain of Cdkl5 KO mice. Treatment with sertraline rescues brain development and behavior in Cdkl5 KO mice.